EDUCAÇÃO FORMAL A ADOLESCENTE SOB PRIVAÇÃO DE LIBERDADE: possibilidades e limites na Educação de Jovens e Adultos no Centro Socioeducativo de Internação Sítio Nova Vida – Paço do Lumiar/MA - BARCELOS, Teresa Neumann Almeida (2022)
This study addresses the formal education of adolescents tailored to deprivation of liberty, in Brazil and Maranhão, seeking to identify the possibilities and limits for the realization of this right provided for in the Statute of Children and Adolescents (ECA), Law 8.069 of 1990, from the Socio-Educational Center for Hospitalization Sítio Nova Vida, in the city of Paço do Lumiar/MA. The study was theoretically supported by historical materialism and, as a result, the dialectical method for apprehending reality, thus seeking to apprehend the historical determinants present in social processes, considering the education of adolescents tailored to deprivation of liberty as a process built. The methodological procedures used were based on the literature review that allowed a theoretical and historical deepening on the subject; research and document analysis; field research through semi-structured interviews with teenagers, technicians from FUNAC and the director and teachers of the school that offers the teaching, in addition to participant observation. The text presented starts from the analysis of the concept of adolescence(s) in the plural, defending the conception of a diversity of adolescents diluted in different social contexts, to, from these historically constructed diversities, analyze the categories of infraction and formal education of adolescent in the context deprivation of liberty, through the Youth and Adult Education (EJA) modality. It also addresses socio-educational care in Brazil and the State of Maranhão, with an emphasis on deprivation of liberty, pointing out schooling data and also considerations on the rights of children and adolescent in the national legal system (Federal Constitution of Brazil of 1988, ECA, National System Educational Service - Sinase) and international organizations to which Brazil is a signatory. It deals with Socio-Educational Measures applied to those who commit an infraction, commenting on Resolutions and other norms that support the most appropriate type of education in the context of deprivation of freedom for adolescent. It analyzes the conditions of the provision of formal education in CSISNV considering a set of subjects involved, concluding that, although EJA presents itself as a possibility of continuing studies by adolescent in compliance with MSE, in the same way as it has been taught in CSISNV, it is still it contains weaknesses, mainly due to the lack of an education policy focused on this audience and the necessary articulation between the Education System and the executing body of the Socio- Educational Measure.